Medidas quânticas, descoerência e emaranhamento em cenários de física de neutrinos - Bittencourt, Victor Augusto Sant Anna Valderramos (2014)
In the first part of this work we describe the cosmological neutrinos as a composite quantum system and use the generalized theory of quantum measurements to acquire a probabilistic correlation between observable energies and flavor eigenstates. We associate flavor averaged and flavor weighted energies to, respectively, selective and non selective quantum measure schemes and avaliate the impact of these definitions in the calculation of a flavor effective mass that determines the neutrino contribution to the energy density of the cosmic inventory. Our results establish that if the cosmic neutrinos state is a maximal mixture all the procedures for the calculation of the energy density will generate the same results. In the second part we turn our attention to the free propagation of flavor states in the wave packet formalism. Interpreting each mass eigenstate, associated to a Gaussian momentum distribution, with a three qubit states, a flavor state is described as a quantum system composed of three subsystems. We consider the different correlations between the quantum superposition components in terms of subtle quantifiers and obtain a coherence scale compatible with the damping scale present in survival probabilities of a flavor, indicating a relation between the damping an the studied correlations. We investigate this relation in terms of the standard deviation between the damping and the density of states associated to the correlation quantifiers a deviation that is minimun only for certain values of the mass eigenstate momentum distribution width.